Undergraduate-community engagement: evidence from UiTM Sarawak / Ellen Chung and Vloreen Nity Mathew - Ellen, Chung; Mathew, Vloreen Nity (Penerbit UiTM (UiTM Press), 2018)
Undergraduate-Community engagement is a form of experiential education in which students engage in activities that address human and community needs. In Malaysia, most undergraduates have at one point or another taken part in community engagement activities. However, the outcome of participating in community engagement has not been properly measured. This study was conducted to investigate the benefits undergraduates gain as a result of community engagement experience, as there is limited studies done in the Malaysian context. This study adopted Student Community Engagement Benefits Questionnaire (SCEBQ) by Chung and Coates (2016). SCEBQ has four benefit constructs, namely career skills, diversity skills, interpersonal skills and civic skills. A total of 143 responses were analysed and results showed that female undergraduates, those who participated in voluntary projects and respondents between 21 to 23 years old reported higher mean gains across the four benefit constructs. Nevertheless, these mean gains did not show any statistically significant difference between gender, community engagement projects types, except age groups. The study is important as it lays the foundation in the process of creating a better understanding of what students learn outside the classroom and it contributes to the practical knowledge of undergraduate-community engagement experience in the context of Malaysian higher education.